2008
DOI: 10.1007/s00264-008-0660-6
|View full text |Cite
|
Sign up to set email alerts
|

Leg lengthening by distraction osteogenesis using the Ilizarov apparatus: a novel concept of tibia callus subsidence and its influencing factors

Abstract: This article studies the incidence and magnitude of delayed callus subsidence, which will also help in study the hypothesis of three cortex corticalisation to determine the time of fixator removal during distraction osteogenesis (DO). Eighty-one tibia segments with mean lengthening of 7.7±2.9 cm were studied with age, gender, skeletal maturity, amount and percentage of lengthening, callus pattern, callus shape, number of cortices seen at the time of fixator removal, bone mineral density (BMD) ratio, and callus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
0
20
0
5
Order By: Relevance
“…A previous study showed that callus subsidence often goes unnoticed by surgeons in spite of the high incidence. 18 It is caused by inadequate callus formation and early weight-bearing, which can also cause axial deviation. Laxity of the knee and ankle and THE JOURNAL OF BONE AND JOINT SURGERY subluxation of the fibular head are more occult complications that many surgeons also overlook.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that callus subsidence often goes unnoticed by surgeons in spite of the high incidence. 18 It is caused by inadequate callus formation and early weight-bearing, which can also cause axial deviation. Laxity of the knee and ankle and THE JOURNAL OF BONE AND JOINT SURGERY subluxation of the fibular head are more occult complications that many surgeons also overlook.…”
Section: Discussionmentioning
confidence: 99%
“…Its measurement and calculation has been well described. [14][15][16][17][18][19][20] The healing index records the time needed to reach a certain level of bone quality for the regenerate. The lower the value, the more ideal the regeneration.…”
Section: Methodsmentioning
confidence: 99%
“…We really appreciate the thoughtful and detailed comments by the readers in referencing our paper on subsidence in tibia lengthening [1].…”
mentioning
confidence: 89%
“…To decrease the amount of time the external fixator was in place, it was often exchanged for a cast prior to complete consolidation. Healing duration was defined as time from the beginning of lengthening until bony consolidation, which was defined by formation of complete cortices at least 2 mm in diameter (three mm for lengthenings under ten centimetres and four mm for lengthening over ten centimetres), as previously described [16,18]. The healing index (healing duration per centimetre of lengthening) was calculated for each patient, and any complications were noted.…”
Section: Assessment Of Healingmentioning
confidence: 99%